Identifikasi Profil Antropometri Atlet Karate Berdasarkan Kelompok Usia di Pontianak - Victor G Simanjuntak; Ahmad Atiq; Dwi Wahyuni Lubiyanti; Sukerman Sukerman; Syarifah Yuliana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
This study aims to identify the anthropometric profiles of karate athletes based on age groups in Pontianak. This study aims to identify the anthropometric profiles of karate athletes based on age groups in Pontianak. This research is a quantitative descriptive study. The sample used in this study was karate athletes in the city of Pontianak, consisting of 45 athletes. Data collection techniques using tests and measurements. Data analysis was assisted by the SPSS version 25 application. The results showed an anthropometric profile of the physical condition of karate athletes in Pontianak city with a normal category average with the following distribution of results and percentages, the less category was 9 people with a percentage of 39%, the normal category with a percentage of 59 % with a total of 35 athletes in the overweight category the percentage is 2% with a total of 1 athlete while for athletes in the obese category the percentage is 0% with the number of athletes being 0. From the results of the measurement tests it can be concluded that the anthropometric profile of karate athletes based on the age group in Pontianak normal category. Keywords: Anthropometry, Athlete, Karate